Emprego de agente complexante e irradiações por feixe de elétrons e laser femtosegundos como estratégias para alterações da propriedade fotoluminescente do α-Ag2WO4 - Santos, Lílian Cruz (Universidade Federal de São Carlos, 2023)
The discovery of room temperature photoluminescence has driven the development of various optical-electronic devices, motivated the search for new photoluminescent materials, and stimulated the modeling of this property through series of changes in synthesis medium. Due to its intrinsic photoluminescence, alpha-silver tungstate (α-Ag2WO4) has been extensively studied with the aim of improving and modifying its use in electronic devices. Morphological and structural modifications, as well as the formation of heterostructures between semiconductors and metallic nanoparticles have been shown to be efficient in photoluminescence modeling and enhancement. Thus, this study aimed at the formation of heterostructures composed of microcrystals of α-Ag2WO4 and Ag nanoparticles, and the morphological and structural modifications of α-Ag2WO4. The silver nanoparticles were obtained by 3 methods: 1) chemical method, in which ethylenediamine was employed as a complexing agent, morphology controller and reducer of Ag+ cation, 2) electron beam irradiation and 3) femtosecond laser irradiation. As results the study highlights the successful structural, morphological and photoluminescence modeling based on the strategies used. The mechanism of particle growth in medium containing ethylenediamine was elucidated and the influence of morphology, surface band gap and microstructure on photoluminescence was discussed according to irradiations employed. Regarding ethylenediamine in the synthesis of α-Ag2WO4, a direct relationship between ethylenediamine concentration and amount of surface silver nanoparticles were observed. And as a consequence of the electronic density of the surfaces constituting each morphology and structural defects, different photoluminescent emission centers were observed for selected strategies.
Employment of complexing agent and irradiation by electron beam and femtosecond laser as strategies for changing the photoluminescent property of α-Ag2WO4
Keywords: Tungstato de prata; Silver tungstate; Agente complexante; Irradiação por feixe de elétrons; Electron beam irradiation; Irradiação por laser femtosegundos; Femtosecond laser irradiation; Fotoluminescência; Photoluminescence; Morfologia; Morphology; Complexing agent; CIENCIAS EXATAS E DA TERRA::QUIMICA; ENGENHARIAS::ENGENHARIA ELETRICA::MATERIAIS ELETRICOS::MATERIAIS E COMPONENTES SEMICONDUTORES; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA